2000
DOI: 10.1007/s003800070030
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocyst(e)inemia induces multiorgan damage

Abstract: Hyperhomocyst(e)inemia has been associated with the development of hypertension, stroke, and cardiovascular, cerebral/neuronal, renal, and liver diseases. To test the hypothesis that homocyst(e)ine plays an integrated role in multiorgan injury in hypertension, we employed: (1) spontaneously hypertensive rats (SHR) in which endogenous homocyst(e)ine levels are moderately high (18.1 +/- ().5 microM); (2) control age- and sex-matched Wistar Kyoto (WKY) rats in which homocyst(e)ine levels are normal (3.7 +/- 0.3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 0 publications
4
70
1
Order By: Relevance
“…In fact, a recent study reported that hyperhomocysteinemia markedly altered the activity of creatinine phosphokinases. 2 Therefore, one should be cautious in using CRc for evaluation of renal function during hyperhomocysteinemia. In a comparable study, McCully demonstrated the possible role of H(e) as an independent risk factor in cardiovascular diseases.…”
Section: Responsementioning
confidence: 99%
“…In fact, a recent study reported that hyperhomocysteinemia markedly altered the activity of creatinine phosphokinases. 2 Therefore, one should be cautious in using CRc for evaluation of renal function during hyperhomocysteinemia. In a comparable study, McCully demonstrated the possible role of H(e) as an independent risk factor in cardiovascular diseases.…”
Section: Responsementioning
confidence: 99%
“…It has been suggested that unfiltered coffee increases plasma homocysteine concentrations in people with normal baseline concentrations. 2,4,5,11,12 Randomized clinical trials suggest that there is a homocysteine-raising effect of both filtered 13 and unfiltered coffee. 2 However, coffee intake in these studies was high (1 l per day) and at these levels of consumption, our results agree with the results of the above studies.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Moreover, although homocysteine levels are lowered by the intake of folate, and vitamins B 6 and B 12 , elevated levels of homocysteine as well have been related with lifestyle habits, such as smoking and alcohol consumption. 1 A randomized clinical trial 3 and some population studies have suggested that a high intake of coffee is associated with raised concentrations of plasma homocysteine.…”
Section: Introductionmentioning
confidence: 99%
“…69 Data from a recent animal study have demonstrated that experimentally induced hyperhomocysteinemia in rats causes endocardial endothelial cell apoptosis and may reduce capillary cell density. 70 Investigators also found structural damage to the aorta, kidney, and renal ureter, which suggests that homocysteineassociated endothelial/epithelial damage is possible in multiple organ systems. 70 C-reactive protein, on the other hand, is believed to be more of a marker than a cause of dysfunction.…”
Section: Risk Factors and Possible Pathogenic Mechanismsmentioning
confidence: 99%
“…70 Investigators also found structural damage to the aorta, kidney, and renal ureter, which suggests that homocysteineassociated endothelial/epithelial damage is possible in multiple organ systems. 70 C-reactive protein, on the other hand, is believed to be more of a marker than a cause of dysfunction. 69 Primary abnormalities of coagulation and platelet function are implicated in only a small percentage of strokes.…”
Section: Risk Factors and Possible Pathogenic Mechanismsmentioning
confidence: 99%